2014
DOI: 10.1371/journal.pone.0086086
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 Arg399Gln Polymorphism Confers Risk of Breast Cancer in American Population: A Meta-Analysis of 10846 Cases and 11723 Controls

Abstract: BackgroundIn the X-ray repair cross-complementing group 1 (XRCC1) gene, a polymorphism, Arg399Gln (rs25487), has been shown to change neoconservative amino acid and thus result in alternation of DNA repair capacity. Numerous studies have investigated the association between Arg399Gln and breast cancer risk in the American population, but yielding inconsistent results. This study aimed to clarify the role of this polymorphism in susceptibility to breast cancer.MethodsLiteratures were searched in multiple databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…Polymorphisms in XRCC1 have been connected to functional changes at the protein level by influencing the DNA repair rate and may results in carcinogenesis (Vodicka et al, 2007). In this study, we have no statistical evident to associate the variant in XRCC1 rs1799782 and rs25487 SNPs to breast cancer risk in Malaysian women but latest metaanalysis studies showed that variant in both SNPs were significantly increased the risk of breast cancer (Wu et al, 2011;Liu et al, 2013;Bu et al, 2014;Feng et al, 2014). Interestingly, a study conducted by Ye et al revealed that breast cancer patients with Gln/Gln genotype in XRCC1 rs25487 SNP were associated with a longer survival rate after chemotherapy treatment when compared to wildtype genotype (Ye et al, 2012), indicating the prognostic value of this SNP in breast cancer patients receiving chemotherapy.…”
Section: 647 Association Of Cyp2e1 Stk15 and Xrcc1 Polymorphisms Wimentioning
confidence: 65%
See 1 more Smart Citation
“…Polymorphisms in XRCC1 have been connected to functional changes at the protein level by influencing the DNA repair rate and may results in carcinogenesis (Vodicka et al, 2007). In this study, we have no statistical evident to associate the variant in XRCC1 rs1799782 and rs25487 SNPs to breast cancer risk in Malaysian women but latest metaanalysis studies showed that variant in both SNPs were significantly increased the risk of breast cancer (Wu et al, 2011;Liu et al, 2013;Bu et al, 2014;Feng et al, 2014). Interestingly, a study conducted by Ye et al revealed that breast cancer patients with Gln/Gln genotype in XRCC1 rs25487 SNP were associated with a longer survival rate after chemotherapy treatment when compared to wildtype genotype (Ye et al, 2012), indicating the prognostic value of this SNP in breast cancer patients receiving chemotherapy.…”
Section: 647 Association Of Cyp2e1 Stk15 and Xrcc1 Polymorphisms Wimentioning
confidence: 65%
“…Taken together, there is significant evidence showing that these three genes are involve in modulating the pathway in the development of breast cancer. Single nucleotide polymorphisms (SNPs) in CYP2E1 (rs6413432 and rs3813867), STK15 (rs2273535 and rs1047972) and XRCC1 (rs1799782 and rs25487) were inconclusively associated to breast cancer risk in case-control or meta-analysis studies in different populations (Wu et al, 2006;Bu et al, 2014;Dai et al, 2014;Ding et al, 2014;Feng et al, 2014;Guo et al, 2014;Qin et al, 2015), but association of these SNPs to breast cancer in Southeast Asia populations, especially in Malaysian women was unquestionably insufficient. Therefore, this pilot study investigates the association of these SNPs, together with etiology factors such as age and ethnicity, to breast cancer risk in Malaysian women.…”
Section: Introductionmentioning
confidence: 99%
“…As we pooled all the individual studies, we compare our result with previous meta-analysis. The last metal analysis of Arg399Gln and risk of breast cancer was done by Bu et al (2014) that included 18 case control studies and just pooled the studies for American population.Their results were similar to our result except that they were able to detect statistically significant association just for certain genetic model (dominant and additive). Another meta-analysis by Wu K. included 44 case and control studies and their finding was similar to our study (they report association under recessive and dominant model) (Wu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who had the Gln allele were reported to be more prone to breast cancer under different genetic model (dominant, recessive and additive). [11,12,13] Yet controversial results were reported, as many studies reported no association between breast cancer and XRCC1 gene polymorphisms, [14] or even decrease of breast cancer risk. [15] NER pathway removes a huge variety of damage to the human genome.…”
Section: Discussionmentioning
confidence: 99%